Enabling unassisted solar water splitting with concurrent high efficiency and stability by robust earth-abundant bifunctional electrocatalysts. (May 2023) - Meng, Xiao; Li, Zaiqi; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Dai, Ying; Huang, Baibiao; Cheng, Hefeng; He, Jr-Hau
Abstract: Hydrogen production from solar water splitting, especially via photovoltaic-electrocatalysis, has been regarded as a promising approach for the conversion of abundant but intermittent solar energy into storable chemical fuels. Despite much progress, conventional combined photoelectrochemical devices usually suffer from severe instability issues, which largely inhibit them for practical applications and may also lead to the uncertain efficiency value for true overall water splitting. Here, we report an unassisted solar water splitting device with concurrent high efficiency and stability, which is constructed by spatial coupling of tandem III-V-based GaInP/GaAs/Ge light absorber and robust earth-abundant Ni foil-based MoNi4 /MoO2 bifunctional electrocatalysts. Remarkably, apart from the outstanding hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) performance, bifunctional MoNi4 /MoO2 electrocatalysts also largely avoid electrode contamination issues, while the robust Ni substrate protects III-Vs from conventional corrosion problems. Consequently, this integrated photovoltaic-electrolysis system device exhibits a high solar-to-hydrogen (STH) conversion efficiency of 17.6 % in alkaline electrolytes with long-term stability of up to 845 h. Further construction into a wireless unassisted monolithic device could lead to an artificial leaf with an STH efficiency of 4.28 %, holding great promise in future solar fuel production with concurrent high efficiency, good stability as well as low cost. Graphical Abstract: A robust earth-abundant Ni foil-based MoNi4 /MoO2 electrocatalyst was rationally designed, working not only as efficient HER and OER bifunctional electrocatalysts but as surface protection material to prevent III-Vs-based solar cells from conventional corrosion issues. Consequently, the integrated monolithic photovoltaic-electrolysis device exhibits a high solar-to-hydrogen conversion efficiency of 17.6 % and long-term stability over 800 h immersed in an alkaline electrolyte. ga1 Highlights: Robust Ni foil-based electrocatalysts greatly reduce costs and improve stability. Coupling of PV and MoNi4 /MoO2 realizes efficient and stable solar water splitting. A wireless artificial leaf is obtained with solar-to-hydrogen efficiency of 4.28 %.